Delay as a Challenge in Prosecuting Non-Compliance in the Halal Industry - Faradina Ahmad; M. Z. Hussein; Z. J. Husny; B. Suleiman; N. Shima; Syazwa Nabila M.R (International Journal of Supply Chain Management, 2017)
This is aresearch identifying the causes and consequence of delay in prosecuting halal industry violation. In determining the reasons for the delay, the authors will look into firstly the procedure and process which shows non-uniformity of legal administration, secondly the scattered laws, policy, standards for the halal industry. The authors will refer to a reported local case law, making comparative study on previous legislation and the current one, to see the elaborated scope of law in relation to the courts decision as a result of delay.